2021
DOI: 10.1136/sextrans-2021-055265
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the time of COVID-19: a quality improvement initiative to maintain services at a youth sexual health clinic

Abstract: ObjectivesAdolescents and young adults (AYAs) face difficulties accessing sexual and reproductive health services. These difficulties were exacerbated for a variety of reasons by the COVID-19 pandemic. We document strategies and outcomes implemented at an urban youth sexual health clinic in Florida that allowed uninterrupted provision of services while protecting against spread of COVID-19.MethodsThe plan–do–study–act (PDSA) model was used to implement COVID-19 interventions designed to allow continued service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Practices need to educate patients on the need to return for regular visits, whether by telehealth or in person, where their reproductive health needs can be addressed. Lim et al found that social media outreach could help compensate for the decrease in face-to-face contact during the pandemic and ensure patients were still aware their providers were there for them (Lim et al, 2021 ). While it is possible that the women who declined the visit truly did not need any further discussion about their reproductive health, this seems highly unlikely given our patient population and the unmet needs we uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Practices need to educate patients on the need to return for regular visits, whether by telehealth or in person, where their reproductive health needs can be addressed. Lim et al found that social media outreach could help compensate for the decrease in face-to-face contact during the pandemic and ensure patients were still aware their providers were there for them (Lim et al, 2021 ). While it is possible that the women who declined the visit truly did not need any further discussion about their reproductive health, this seems highly unlikely given our patient population and the unmet needs we uncovered.…”
Section: Discussionmentioning
confidence: 99%